Work interruptions resiliency: toward an improved understanding of employee efficiency. Issue 1 (13th March 2017) - Zide, Julie S.; Mills, Maura J.; Shahani-Denning, Comila; Sweetapple, Carolyn
Abstract : Purpose: The purpose of this paper is to operationalize the construct of work interruptions resiliency (WIR) and develop a measure assessing the extent to which employees report resiliency in resumption of work activities post-interruption (Study 1), and to further examine WIR's nomological net, specifically its predictive relations with important employee-level outcomes (Study 2). Design/methodology/approach: Study 1 utilized subject matter experts and data from 274 employees from a range of industries for scale development. Study 2 utilized 365 registered nurses from a hospital network to confirm and extend the findings from Study 1 within a relevant, dynamic job type. Findings: Study 1 yielded a psychometrically sound measure for WIR comprised of four factors (typical, critical, external, sensory). Validity was evidenced via negative correlations with cognitive demand and Type A personality, and positive correlations with conscientiousness. Study 2 expanded WIR's nomological net by evidencing its predictive relations with employees' role clarity, autonomy support, role breadth self-efficacy, and evidence-based practice adoption intentions. Research limitations/implications: This research introduces WIR and develops a measure for assessment, providing validity evidence and establishing an initial nomological net for WIR upon which further research can rely and build. Practical implications: The work interruptions resiliency construct and measure have the potential to impact selection and training, particularly in job types wherein poor recovery from interruptions can yield detrimental consequences. Originality/value: Work interruptions compromise productivity and result in errors. It is therefore crucial that organizations assess the extent to which employees are resistant to the detrimental effects of such disruptions (Study 1) and understand the nature of WIR's predictive relations with important employee-level outcomes (Study 2).